Immunology of the bovine uterus and immunological strategies to resolve endometritis - DHALIWAL, G S; SIDHU, S S (The Indian Journal of Animal Reproduction, 2023)
Endometritis in breeding cattle· occurs during the postpartum period, and is mostly associated withascending infection involving Arcanobacter pyogenes together with Gram negative anaerobes. Part of the uterinedefence mechanisms against bacterial invasion is provided by uterine polymorphonuclear leukocytes (PMNs),whose phagocytic activity depends on bacterial opsonisation by humoral antibodies. The leukocyte count in theuterine lumen is relatively high during the met-oestrus period compared to other phases of the oestrus cycle.Humoral immune response in the bovine reproductive tract is stimulated following local antigen exposure, and theresponse is site dependent; lgG predominates in the uterus while IgA in the vagina. A part of IgG 1 is synthesisedlocally in the bovine endometrium while the remaining IgG 1 and whole of the lgG2 in the uterine lumen is derivedfrom the uterine blood circulation. Intrauterine infusion of immunomodulators, such as E. coli lipopolysaccharides(LPS) or oyster glycogen, in healthy cows and those with endometritis, induces leukocytosis within the uterinelumen; leukocyte count is relatively high during dioestrus but their functional activity is not affected by the stageof the oestrous cycle. Uterine luminal immunosuppressant proteins elevate under progesterone dominance. whichinhibit lymphocyte proliferation, thereby making the uterus more susceptible to infections. Exact mechanismsinvolved in the increased susceptibility of the uterus to infections during the luteal phase of the oestrous cycle arestill not clear. E. coli lipopolysaccharides (LPS) when administered intrauterine at a dosage of 100 mg, are notabsorbed by the healthy endometrium. and do not alter the oestrous cycle length. It is not known whether this doseof LPS will be absorbed from the inflamed uterus of naturally occurring cases of endometritis, and will causesystemic illness.
Keywords: Endometritis, bovine; immwiom&dulators; uterine defence